Ireland : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
The 2006 Article IV Consultation found that the financial system in Ireland continues to perform well but rapid credit growth is a vulnerability. Central Bank officials noted that recent stress tests indicate that the major lenders have adequate buffers to cover a range of shocks. The Financial Regulator observed that the risk weighting on high loan-to-value mortgages was increased, consistent with the advice of the Financial Sector Assessment Program (FSAP) Update mission. The general government fiscal position has been either close to balance or in surplus for the past decade.